Digital-Age Leadership of School Administrators Based on the Four Brahmavihra Principles Under the Khon Kaen Primary Educational Service Area Office 2 - Wongjunla, Junthida; Saikham, Sunthon; Chotivungso, PhrakhrupaladBoonchuay (Journal of Graduate MCU KhonKaen Campus, 2026)
This research aimed to study the digital-age leadership of school administrators based on the Four Brahmavihra principles under the Khon Kaen Primary Educational Service Area Office 2, and to explore recommendations for the development of digital leadership of school administrators based on the Four Brahmavihra principles under the Khon Kaen Primary Educational Service Area Office 2. This study employed a mixed-methods research design, consisting of quantitative research through questionnaires with a sample of 419 participants, and qualitative research through interviews with nine key informants. Quantitative data were analyzed using basic statistics, while qualitative data were analyzed using content analysis. The findings of the research were as follows: 1. The digital-age leadership of school administrators based on the Four Brahmavihra principles under the Khon Kaen Primary Educational Service Area Office 2 was overall at a high level. Ranked from highest to lowest were: digital literacy based on the Four Brahmavihra principles; digital communication based on the Four Brahmavihra principles; digital vision based on the Four Brahmavihra principles; and digital professionalism based on the Four Brahmavihra principles. 2. The guidelines for developing the digital-age leadership of school administrators based on the Four Brahmavihra principles under the Khon Kaen Primary Educational Service Area Office 2 include the following: in terms of digital vision based on the Four Brahmavihra principles, administrators collaborate with teachers and personnel to establish concrete digital policies and shared agreements; in terms of digital communication based on the Four Brahmavihra principles, administrators use digital media as a channel for meetings or collaborative brainstorming in work processes; in terms of digital professionalism based on the Four Brahmavihra principles, administrators support the creation of knowledge and the use of modern digital technology in management; and in terms of digital literacy based on the Four Brahmavihra principles, administrators promote and support the availability of adequate digital technology for use within the school.